Use Database to Evaluate the Prevalence of Hunger Among Adolescents in Brazil - Amorim, Ana Laura Benevenuto de; Ribeiro Junior, José Raimundo Sousa; Gonçalves, Helida Ventura Barbosa; Bandoni, Daniel Henrique (Frontiers in Nutrition, 2021)
Food insecurity and malnutrition have become serious problems in many countries. In recent years, Brazil has experienced an increase in the prevalence of food insecurity and hunger. However, there is limited information on the status of these issues, and food security assessments are only performed as household measures. Therefore, the use of available databases is essential to expand information and support decision-making in the fight against food insecurity. This study aimed to evaluate the relationship between reports of hunger among adolescents and their sociodemographic characteristics. We used data from the 2015 National School Health Survey. The main variable of interest was obtained from responses to the following question: “Over the past 30 days, how often have you gone hungry because you did not have enough food at home?”. The responses were separately gathered from those who reported going hungry and those who did not. Socioeconomic characteristics were evaluated simultaneously. For statistical analysis, a Pearson chi-square test and multiple analyses were performed using Poisson regression models. A total of 101,888 adolescents were evaluated. The variable used to measure hunger was associated with maternal education, internet access, and fruit intake. The results showed a positive association between adolescents who reported going hungry and women, black and indigenous adolescent students living in households with more than five people, adolescents not living with their father, and adolescents planning to work or not knowing what they will do after completing the ninth grade. The results demonstrate that it is possible to use secondary data with a single question to assess, monitor, and provide insights into how food security impacts the sociodemographic groups differently.